Molecular floating-gate single-electron transistor - Makoto Yamamoto (Nature Portfolio, 2017)
Abstract We investigated reversible switching behaviors of a molecular floating-gate single-electron transistor (MFG-SET). The device consists of a gold nanoparticle-based SET and a few tetra-tert-butyl copper phthalocyanine (ttbCuPc) molecules; each nanoparticle (NP) functions as a Coulomb island. The ttbCuPc molecules function as photoreactive floating gates, which reversibly change the potential of the Coulomb island depending on the charge states induced in the ttbCuPc molecules by light irradiation or by externally applied voltages. We found that single-electron charging of ttbCuPc leads to a potential shift in the Coulomb island by more than half of its charging energy. The first induced device state was sufficiently stable; the retention time was more than a few hours without application of an external voltage. Moreover, the device exhibited an additional state when irradiated with 700 nm light, corresponding to doubly charged ttbCuPc. The life time of this additional state was several seconds, which is much shorter than that of the first induced state. These results clearly demonstrate an alternative method utilizing the unique functionality of the single molecule in nanoelectronics devices, and the potential application of MFG-SETs for investigating molecular charging phenomena.